PENGARUH RUANG TERBUKA HIJAU (RTH) TERHADAP KENYAMANAN TERMAL DI PERUMAHAN: STUDI KASUS: PERUMAHAN TASBI 1 MEDAN - Sibarani, Paterson HP; Martha Mulia, Endi; Gulo, Hermanto; Ayunani, Syafira; Vera Lokita, Valentina (LPPM ISTP, 2025)
ABSTRACT Thermal comfort is a key indicator of residential environmental quality, particularly in tropical regions characterized by high temperatures and fluctuating humidity. This study aims to analyze the influence of green open space (RTH) on thermal comfort in the TASBI 1 Housing Complex in Medan. A quantitative descriptive approach was employed over five consecutive days, involving measurements of air temperature, relative humidity, and wind speed in two zones with differing levels of vegetation density. The results show that the presence of RTH significantly reduces the average daytime temperature by 5.3°C and increases relative humidity in the afternoon by 7.2%. Zones with dense vegetation exhibit cooler and more humid microclimates compared to areas with minimal RTH. Additionally, residents in high-RTH zones reported lower usage of air conditioning, indicating the role of vegetation in promoting energy efficiency. This research highlights the importance of integrating green elements into residential planning to create more comfortable, energy-efficient, and sustainable living environments.